Determinants of internal versus external R&D offshoring: Evidence from Spanish firms (2014)
This paper analyzes the determinants of R&D offshoring of Spanish firms using information from the Panel of Technological Innovation. We find that being an exporter, continuous R&D engagement, applying for patents, being a subsidiary, and firm size are factors that positively affect the decision to offshore R&D. In addition, we obtain that the factors that influence this decision for firms that belong to a business group differ depending on whether the firm purchases R&D services within the group or through the market: the lack of information is an obstacle relatively less important for internal R&D offshoring than for external R&D offshoring, while a higher degree of importance assigned to institutional and market sources of information for innovation as compared to internal sources increases the probability of R&D offshoring through the market.